Marital Adjustment and Mindfulness Among Married Individuals: The Mediating Roles of Emotional Intelligence and Sexual Satisfaction - Kaya, Yagmur; Erus, Seher Merve; Deniz, M. Engin; Rustamov, Elnur (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
Marital adjustment is a critical determinant of mental health and relational stability. Therefore, examining the factors that contribute to marital adjustment is of great importance. This study aimed to examine the relationships among mindfulness in marriage, marital adjustment, emotional intelligence, and sexual satisfaction in married individuals. Structural equation modeling revealed that the relationship between mindfulness in marriage and marital adjustment was mediated by emotional intelligence and sexual satisfaction. These findings provide empirical support for theoretical models emphasizing relational mechanisms and indicate that integrating mindfulness, emotional intelligence, and sexual satisfaction into marital and couples counseling interventions could be particularly beneficial.
Keywords: Marital adjustment; mindfulness in marriage; emotional intelligence; sexual satisfaction; married individuals; VALIDATION; FREQUENCY; QUALITY; Psychology; Family Studies